Upaya Meningkatkan Hasil Belajar Siswa Materi Perpindahan Kalor Dalam Kehidupan Sehari-Hari Melalui Metode Eksperimen Di Kelas Vb MIN 1 Pangkalpinang Semester II Tahun Pelajaran 2019-2020 - Astuti, Susmi; Tantri, Tantri (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2022)
This research is motivated by the low learning outcomes of students and students are less active in learning class Vb MIN 1 Pangkalpinang Bangka Belitung. The researcher formulates a problem formulation, namely whether using the experimental method can improve student learning outcomes in heat transfer material in everyday life in class Vb semester II MIN 1 Pangkalpinang for the 2019 - 2020 school year?. The main objective in this study is to improve learning outcomes on heat transfer material in everyday life in class Vb MIN 1 Pangkalan Pinang. This research is a Classroom Action Research (CAR) which uses an experimental method. This research was carried out in 2 cycles which were carried out in the period from January to June 2019. Each cycle consisted of 4 stages, namely starting from the planning, implementation, observing and reflecting stages. The data collection instruments in this study were student and teacher observation sheets and knowledge assessment sheets The results showed an increase in student learning outcomes which were as follows: in the first cycle it was 50% then increased to 96.66% in the second cycle. in class Vb semester II MIN 1 Pangkalpinang academic year 2019 - 2020